2017
DOI: 10.1093/jcr/ucx061
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Witnessing Moral Violations Increases Conformity in Consumption

Abstract: This research is based on part of the first author's doctoral dissertation under the guidance of the second author. The authors gratefully acknowledge the financial support from the Sheth Foundation through the 2015 ACR/Sheth Foundation Dissertation Award and the Social Sciences and Humanities Research Council of Canada. We thank Bob Wyer and Avni Shah for their insightful comments. We also thank Rachel Hung, Keiron Narine, Zohra Abdul Razaq, and Jenny Wang for their excellent assistance in data collection. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Two hundred twenty-two US adult consumers participated in this experiment on Amazon Mechanical Turk (MTurk). Two participants indicated that they were heavily distracted during the study and thus were excluded from later data analyses (Dong and Zhong 2017;Oppenheimer, Meyvis, and Davidenko 2009), leaving 220 participants in the sample (M age ¼ 36.4; 55.5% female). In this and later studies, exclusion of distracted participants did not significantly change the data pattern we report.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred twenty-two US adult consumers participated in this experiment on Amazon Mechanical Turk (MTurk). Two participants indicated that they were heavily distracted during the study and thus were excluded from later data analyses (Dong and Zhong 2017;Oppenheimer, Meyvis, and Davidenko 2009), leaving 220 participants in the sample (M age ¼ 36.4; 55.5% female). In this and later studies, exclusion of distracted participants did not significantly change the data pattern we report.…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred fifty-one US adults from MTurk participated in the experiment for a nominal payment. Three participants were excluded from further analyses because they indicated that they were distracted during the study (Dong and Zhong 2017;Oppenheimer et al 2009). This left 248 participants in the final sample (M age ¼ 36.4; 47.2% female).…”
Section: Methodsmentioning
confidence: 99%
“…Park and Feinberg [10] explained that the opinions of the people around them are the decisive variables that cause an individual's conformity consumption. Dong and Zhong [21] suggested that jointly engaging in synchronous activities can activate a general "copying others" mindset, resulting in increasing conformity tendencies.…”
Section: Conformity Consumption Of Culturally Associated Brandsmentioning
confidence: 99%
“…This formulation is extremely congenial to a system justification perspective, which suggests that people engage in a wide variety of behaviors-including consumer behaviorsto satisfy the quintessentially ideological goal of maintaining (or restoring) the legitimacy of the overarching social system (e.g., Banfield et al, 2011;Cutright et al, 2011;Dong & Zhong, 2017;Liviatan & Jost, 2014;Shepherd et al, 2015).…”
Section: Implications For Persuasion Framing and Advertisingmentioning
confidence: 99%